2019
DOI: 10.20525/ijrbs.v8i6.527
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tax planning on financial performance of manufacturing companies listed at Nairobi Securities Exchange

Abstract: Taxes form a significant portion of a company’s expenses and in order to increase probable returns, tax planning is vital to financing and investment decisions of an entity. This study sought to find out the influence of tax avoidance on financial performance of all the nine manufacturing firms listed on the Nairobi Securities Exchange during the period 2010-2017. The study was anchored on tax planning theory, capital structure trade-off theory, agency cost theory and political power theory. The study adopted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Hypothesis four shows that there is a positive and significant relationship between corporate size and corporate financial performance of insurance companies in Nigeria. The positive findings between corporate size and corporate financial performance conforms to the findings in the study of Oeta, et al (2019); Timothy, et al (2020) which reveal that corporate size positively affects the value of firms. The findings disagree with the study of Banchuenvijit (2012); Nwaobia, et al (2016) that showed a negative association between corporate size and value of a firm.…”
Section: Discussion Of Findingssupporting
confidence: 86%
See 1 more Smart Citation
“…Hypothesis four shows that there is a positive and significant relationship between corporate size and corporate financial performance of insurance companies in Nigeria. The positive findings between corporate size and corporate financial performance conforms to the findings in the study of Oeta, et al (2019); Timothy, et al (2020) which reveal that corporate size positively affects the value of firms. The findings disagree with the study of Banchuenvijit (2012); Nwaobia, et al (2016) that showed a negative association between corporate size and value of a firm.…”
Section: Discussion Of Findingssupporting
confidence: 86%
“…The results contradict the findings of De Jong et al (2011) and Gonzales (2013) revealed that debt positively influences the value of a company. Oeta, et al (2019), Timothy, et al (2020), Izevbekhai & Odion (2018); Razali, et al (2018) findings suggest a negative insignificant relationship between financial leverage and value of a firm.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Market value, otherwise defined as market capitalisation is computed as the product of outstanding shares and market price at a point in time. Companies with higher market capitalisation are considered to have a higher firm value (Oeta et al, 2019). Tobin's Q has also been adopted a measure of firm value in literature (Bhagiawan & Mukhlasin, 2020;Kiesewetter & Manthey, 2017;Nafti, Kateb, & Masghouni, 2020;Omesi & Appah, 2021).…”
Section: Firm Valuementioning
confidence: 99%
“…First, the previous literature focuses on EBIT and EBITDA as performance metrics but does not use these parameters in investment-intensive firms such as those in this study. The majority of these studies (e.g., Ester and Ballkoci, 2017;Chukwu and Egbuhuzor, 2017;Amoroso et al, 2017;Oeta et al, 2019) used other parameters, such as ROA and ROE, which are calculated and influenced by GAAP rules. To avoid the effect of GAAP parameters on investment, this study uses non-GAAP metrics: EBITDA and EBIT.…”
mentioning
confidence: 99%
“…Chukwuma et al (2022) argued that profitability is important for the survival and increase in the scale of business to achieve the final goal of growth. Profitability is measured by many proxies, such as return on assets (Ester and Ballkoci, 2017), return on equity (Chukwu and Egbuhuzor, 2017), operating income (Amoroso et al, 2017), and earnings (Oeta et al, 2019). To the best of the authors' knowledge, only one prior study used a different proxy to measure profitability, that is, earnings before tax, interest, depreciation, and amortization (EBITDA).…”
mentioning
confidence: 99%